PENGARUH KOMITMEN AFFEKTIF DAN KUALITAS KINERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PALEMBANG - Mohd. Kurniawan DP (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2021)
This study aims to analyze the effect of affective commitment and performance quality on employee job satisfaction at the Palembang City Population and Civil Registration Service. Data for 106 respondents were collected through a questionnaire and analyzed using multiple linear regression methods. The results of the investigation show that partially each affective commitment and performance quality have a significant effect on job satisfaction. Likewise, simultaneously affective commitment and performance quality have a significant effect on job satisfaction. These empirical findings can be useful for the Palembang City Population and Civil Registration Service. Leaders in this government agency should pay attention to the factor of affective commitment and quality of performance to optimize employee performance.